2004
DOI: 10.1111/j.1365-2249.2004.02550.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased interferon-αproduction and impaired T helper 1 polarization by dendritic cells from patients with chronic hepatitis C

Abstract: SUMMARYPatients with chronic hepatitis C (CHC) are unable to prime and maintain vigorous T cell responses that are initiated during the acute phase of hepatitis C virus (HCV) infection. As dendritic cells (DCs) induce and regulate both innate and adaptive immune responses, the aim of this study was to analyse two critical functions of DCs: firstly, production of interferon (IFN)-a and, secondly, polarization of T helper 1 lymphocytes. The frequencies of plasmacytoid DC (PDC) and myeloid DC (MDC) were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 29 publications
9
50
0
6
Order By: Relevance
“…Reduced absolute numbers of the circulating PDCs were reported previously in patients with chronic HCV compared with controls (23)(24)(25). A HCV escape mechanism from IFN-␣-mediated antiviral effects would be most important in the liver, where HCV replicates and most of the virus and the virus-derived proteins are produced.…”
Section: Discussionmentioning
confidence: 89%
“…Reduced absolute numbers of the circulating PDCs were reported previously in patients with chronic HCV compared with controls (23)(24)(25). A HCV escape mechanism from IFN-␣-mediated antiviral effects would be most important in the liver, where HCV replicates and most of the virus and the virus-derived proteins are produced.…”
Section: Discussionmentioning
confidence: 89%
“…It is notable that in HIV infection, there is a reduction in the number of plasmacytoid DCs (which produce high levels of IFN-␣/␤) in the peripheral blood (71). Although in HCV infection, pDC numbers are not dramatically reduced, their IFN-␣ production capacity may be impaired (6,62). A recent study also suggested that there may be abnormalities in the ability of DCs from HCV ϩ patients to produce IL-15 in response to IFN-␣ stimulation (43).…”
Section: Cd28mentioning
confidence: 99%
“…98,102,103 More importantly, while the amounts of IFN-␣ produced in vivo are insufficient to modulate the antigen-processing and antigen-presenting functions, they are certainly sufficient for transforming the PDCs into potent activators of adaptive immunity during chronic HCV infection. As reported by Murakami et al, 102 PDCs from patients with HCV induced significantly lower numbers of IFN-␥-producing effector T lymphocytes compared with that of controls. Furthermore, PDCs of patients primed more CD4 T cells producing IL-10 than those from normal controls.…”
Section: Dendritic Cells In Hcv Infectionmentioning
confidence: 99%